Characteristics of nerve graph: a view from graph terminologies - Aziz, Nur Atikah; Yusof, Yuhani; Sarmin, Nor Haniza; Mohd Radzuan, Hazulin; Noviantri, Viska (Universiti Malaysia Pahang Al-Sultan Abdullah Press, 2025)
In this study, the characteristics of nerve graph are investigated through graph theory. This study addresses the problem of identifying and characterizing nerve graph from the perspective of simple, degree, bipartite, adjacency and cycles terminologies. Employing the proof-by-cases method, this article systematically analyses the characteristics of the nerve graph and reveals distinct features based on its structural configurations. This research significantly contributes to graph theory field by enhancing the understanding of nerve graph and paving the way for further research and practical applications.